'Human rights' in the discourse of Buraku liberation: from the 1920s to the 1990s, an initial survey - Neary, I (Institute for Social Development and Policy Research, 2010)
The paper argues that ideas about human rights, rather than being a relatively new arrival within political and social discourse, have been present in both the mainstream and the dissenting streams of Japan’s political system since the start of the twentieth century. In the years immediately after the war human rights were explicitly promoted by the US occupation and adopted enthusiastically by the Japan Socialist Party and those involved in the Buraku liberation movement such as Matsumoto Jiichiro. During the 1950s, however, this enthusiasm dissipated in the face of the cold war intolerance of government and a focus on policies that could address the relative and absolute poverty experienced by the discriminated Buraku. Only in the post cold war 1990s did the state and the liberation movement once more start to take human rights seriously. Human rights have been present in Japan for well over a century but their impact on political and social practice has varied greatly depending on the complex interplay between domestic social and political factors and the international environment – just as in most other countries around the world.